PENERAPAN MODEL PEMBELAJARAN MIND MAP UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IIIA SDN 034 TARAIBANGUN - Pardamean Tua Uli Tua Uli; Erlisnawati '; Jesi Alexander Alim Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Base of problem in this research is the value of the students still under KKM. It is unknown, because the teacher does not involve students in the learning process, the teacher does not use the media during the learning process to take place, many students who are less interested in the teaching-learning process because it is considered less interesting, and presence of dependent students to other students who are superior. For it to be done learning improvement by application of model learning Mind Map. Model Learning Mind Map is a form of learning model that prioritizes theme lesson assembled with nets-nets full of variations to facilitate the students remember information subjects received. The application of model learning Mind this folder aims to let students learn with learning model that prioritizes theme lesson assembled with nets-nets full of variations to facilitate the students remember information subjects received. This research in the form of a class Action Research (PTK). This research aims to improve the learning results of grade IIIA SD Negeri Taraibangun 034. After the application of the model of learning Mind Folder can be applied, data obtained from quantitative data. With the formulation of a problem is